FrogAncestryCalc: A standalone batch likelihood computation tool for ancestry inference panels catalogued in FROG-kb. (May 2020) - Rajeevan, Haseena; Soundararajan, Usha; Pakstis, Andrew J.; Kidd, Kenneth K.
Highlights: FrogAncestryCalc is the stand-alone version of FROG-kb. Simultaneously computes population likelihoods for multiple individuals. Five Ancestry Inference (AI) panels are implemented. Available for download from FROG-kb and GitHub. FrogAncestryCalc is open source. Abstract: The web-based application, FROG-kb (the Forensic Resource/Reference on Genetics-knowledge base, https://frog.med.yale.edu ) supports the use of Single Nucleotide Polymorphisms (SNPs) for individual identification and ancestry inference in a forensic setting. The primary functionality provided by FROG-kb on the web is computation of relative likelihoods of populations being the origin of an individual, utilizing the underlying reference population allele frequency data curated and organized in ALFRED, the ALlele FREquency Database (https://alfred.med.yale.edu/ ). Here we present a downloadable stand-alone tool, FrogAncestryCalc that can simultaneously compute population likelihoods for multiple individuals for a selected panel of SNPs. The program calculates for a given Ancestry Inference (AI) panel the probability of each individual's genotype profile arising in each of the reference populations. Five of the AI panels catalogued in FROG-kb are implemented in this version of FrogAncestryCalc.